Interpretation of Water Quality Based on Seawater Intrusion Data in Ongkowa Takalar Village - Nurul Amelia Malik; Muhammad Arsyad; Sulistiawaty Sulistiawaty (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2025)
Ongkowa Hamlet Takalar is a settlement located approximately 500 m from the beach, where the local community still depends on wells at a depth of about 3-5 m as a source of clean water, so it has the potential to experience seawater intrusion. This study aims to analyze well water quality, the structure of the subsurface layer using the Wenner-Schlumberger resistivity method, and interpret the distribution of seawater intrusion based on resistivity and water quality data. In this study, resistivity measurements were carried out on 3 tracks using the GL-4100 Resistivity meter. Water quality testing on 4 water well samples and 1 seawater sample in the laboratory. The resistivity measurement point is located at a distance of 110-1712 meters from the coast, while the well water sampling point is 222-1813 meters from the coast. The results showed salinity levels of 74.348-376.74 mg/L, DHL 26.2-130.7 μS/cm, and TDS 20.9-104.3 mg/L. Well water at the study site is still classified as freshwater and eligible for consumption, with no indication of seawater intrusion. The subsurface lithology consists of limestone, sand and gravel, and basalt. Seawater intrusion was found in limestone with low resistivity at a depth of 3.85-6.75 m located 202 m from the coast, and at a depth of 2-15.9 m, located 100 m from the coast. Well water at a depth of about 3 m at a distance of 220 m from the coast is still classified as fresh water.